Corporate Social Responsibility in Sri Lanka: A case for Peacebuilding - Santhirakumaran, Gajendrakumar (2007)
Violent conflict has plagued Sri Lanka for much of the last half-century. There have been several axes of conflict, some of which became militarised (the Janatha Vimukthi Peramuna insurgencies in the 1970s and 1980s, and the current war with the Liberation Tigers of Tamil Eelam, or LTTE), and some that remained latent (the grievances of the Malayaga or ‘Hill Country’ Tamils, for example). A legacy of militarised violence, assassinations, state repression and ‘party political’ violence has impacted on all aspects of Sri Lankan society. As a consequence, the socio-political and, to some degree, the economic fabric of the country is fragile at best.